Development of the Theory of Capitalist Crises: Political Economy Traditions and Modernity - Ryazanov, Viktor Timofeyevich (Economy of Regions, 2015)
The article discusses the development history of the theory of economic crises under capitalism conditions. The author believes that economic science is being developed in two directions. The first direction is represented by science schools that deny any objective grounds for crises of overproduction in the market economy and develop new models of crisis-free growth. The opposite direction is supported by science schools acknowledging the existence of objective causes of crises, which is of practical significance for development of effective anti-crisis measures. The study is summarized by the conclusion about actualization of the political economy approach to analysis of the recent global crisis and its consequences. Its implementation anticipates special attention to different versions of overaccumulation of capital which played a key role in the origin of crisis processes in the world economy.